Ecological engineering in cauliflower for aphid management - Keerthi, M C; Sharma, R K; Suroshe, Sachin S; Sinha, S R (The Indian Journal of Agricultural Sciences, 2020)
Because of high-value, the crops like Brassica have very low pest-damage thresholds, natural enemies alone are unlikely to replace use of high cost insecticides. However, conservation of natural enemy population is possible by avoiding or applying insecticides at reduced rates and use of habitat manipulation techniques such as ecological engineering, used in the present research work. The selected flower crops apart from hosting natural enemy it is also an alternate source of income to farmers. Among the intercrops, cineraria flower crop reported with less number of aphids and even attracted more number of syrphids as well as coccinellids can be exploited to use as intercrop.